Development of Single Phase Back to Back Converter with Closed Loop Voltage Feedback Controlled by Arduino Microcontroller - Zulkifi, Shamsul Aizam; Zakaria, Mohd Zulfahmi (International Journal of Integrated Engineering, 2016)
This paper presents a development of single phase back to back converter using voltage closed loop feedback using Arduino microcontroller. The key feature of this system is the ability of the Arduino as a low microcontroller to control the gate signal of power switches of the inverter by referring to the target voltage when applying with the PI control. The Matlab-Simulink has been the communication medium between software and the microcontroller. This is because, the controller structures have been developed based on the control mathematical formulae before downloaded to the microcontroller in order to test the back to back converter. Based on the results obtained, the back to back converter has successfully responded to the voltage feedback control mechanism and the Arduino is operated as a suitable low cost microcontroller for gate firing signals